Ecological footprint as a tool for change of individual attitudes toward the environment and better education for sustainability - Veselaj, Zeqir; Berisha, Shahin (Technium Social Sciences Journal, 2022)
One of the most direct and easy to be use indicators of individual sustainability to date is the Ecological Footprint. The Ecological footprint measures how much bio productive area (whether land or water) a population would need to produce to sustain the renewable resources it consumes, and to absorb the waste it generates. The purpose of this research is, in addition to a self-assessment of the students’ knowledge about the basic concepts of individual sustainability such Ecological footprint, biocapacity, Carbon footprint, Water footprint and Earth Overshoot Day, to undertake the first calculation of the individual ecological footprint in Kosovo. The research hypothesis was that the Ecological footprint of our group would be below the global average of 2.8 global hectares (gha). The sample of this research consists of 240 students of the Faculty of Education, University of Prishtina. With this calculation, students have shown their individual impact in the environment according to their lifestyle: housing, food, travel, purchase of goods and how much waste they generate. The data have shown that the average Ecological footprint of the sample is 3.4 gha, with a minimum value of 2.5 gha and a maximum of 5.3 gha. This figure is 0.6 gha above the global average Ecological footprint and larger than three neighboring countries of Kosovo. The largest percentage of the group’s footprint is transportation, followed by housing, food, waste, and purchases of goods.